2015
DOI: 10.1002/ab.21638
|View full text |Cite
|
Sign up to set email alerts
|

Soccer players awarded one or more red cards exhibit lower 2D:4D ratios

Abstract: Anatomical, cognitive and behavioral sex differences are widely recognized in many species. It has been proposed that some of these differences might result from the organizing effects of prenatal sex steroids. In humans, males usually exhibit higher levels of physical aggression and prowess. In this study, we analyze the relationship between second-to-fourth digit (2D:4D) ratios-a proxy for prenatal androgen levels-and foul play and sporting performance in a sample of junior soccer players from a professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…There is certainly some evidence for this in male sport. For example, elite football players with low 2D:4D tend to be more aggressive and commit more fouls per game (punished by the referee as a caution [yellow card] or as an expulsion [red card]) than players with high 2D:4D (Mailhos, Buunk, Del Arca & Tutte, ; Perciavalle, Di Corrado, Petralia, Gurrisi, Massimino & Coco, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is certainly some evidence for this in male sport. For example, elite football players with low 2D:4D tend to be more aggressive and commit more fouls per game (punished by the referee as a caution [yellow card] or as an expulsion [red card]) than players with high 2D:4D (Mailhos, Buunk, Del Arca & Tutte, ; Perciavalle, Di Corrado, Petralia, Gurrisi, Massimino & Coco, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the negative association between a man's 2D4D ratio and the frequency of M-A produced suggests that pT concentrations may influence the use of metaphorical language to signal mate quality. A low 2D4D ratio is indicative of higher pT (Lutchmaya et al, 2004 ) as well as higher sexual-interest and male specific traits (Klimek et al, 2014 ; Mailhos et al, 2016 ). A recent large-scaled study including 89,612 men has also shown significant association between 2D4D ratio and male-type occupations (Manning et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between pT and language ability remains controversial (Papadatou-Pastou and Martin, 2017 ). Higher pT concentrations are also associated with more masculine behavior (Aromäki et al, 2002 ; Bancroft, 2005 ; Auyeung et al, 2009 ; Welker et al, 2014 ; Kung et al, 2016 ; Mailhos et al, 2016 ; Atkinson et al, 2017 ), indicative of a man's physical and reproductive health (Johnston et al, 2001 ; Klimek et al, 2014 ), and a stronger sex drive (Aromäki et al, 2002 ). Thus, the propensity for men to use language to display their mate quality might vary as a function of individual differences in pT levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to take into account that in the majority of the studies adopted in these meta-analyses aggression is measured in artificial settings or by self reports in questionnaires. Again, “real-world” aggressive behavior during sport contests seems to be more consistently related to 2D:4D (Perciavalle et al, 2013 ; Mailhos et al, 2016 ). Furthermore, typical studies focus on linear relationships between 2D:4D and aggression without taking the context into account.…”
Section: Introductionmentioning
confidence: 99%